2015
DOI: 10.1021/ma5025945
|View full text |Cite
|
Sign up to set email alerts
|

Confined Nucleation and Crystallization Kinetics in Lamellar Crystalline–Amorphous Diblock Copolymer Poly(ε-caprolactone)-b-poly(4-vinylpyridine)

Abstract: The nucleation and crystallization kinetics of lamellar crystalline−amorphous diblock copolymer poly(ε-caprolactone)-b-poly(4-vinylpyridine) (PCL−P4VP) was investigated by ultrafast differential scanning calorimetry (UFDSC) with temperature scanning rates up to 10 000 K/s and compared with that of poly(ε-caprolactone) (PCL) homopolymer. We found that the critical cooling rate (ccr) to get the fully amorphous PCL is 1 order of magnitude slower than that for PCL homopolymer with the similar molecular weight. Iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 51 publications
1
22
0
Order By: Relevance
“…Consequently, the crystalline block crystallizes within hard (or glassy) nanodomains to form crystalline microdomain structures [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34]. It is generally observed for the crystallization in hard nanodomains that the melting temperature is considerably low and the final crystallinity is extremely small as compared with the case in the crystalline lamellar morphology formed by break-out crystallization (Fig.…”
Section: Crystallization In Hard Nanodomainsmentioning
confidence: 97%
“…Consequently, the crystalline block crystallizes within hard (or glassy) nanodomains to form crystalline microdomain structures [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34]. It is generally observed for the crystallization in hard nanodomains that the melting temperature is considerably low and the final crystallinity is extremely small as compared with the case in the crystalline lamellar morphology formed by break-out crystallization (Fig.…”
Section: Crystallization In Hard Nanodomainsmentioning
confidence: 97%
“…The parameter n of PVDF component in blends is almost the same as that in pure PVDF, suggesting that the PMMA-b-P2VP content has little influence on the crystallization mechanism of PVDF. What is more, it is found in Table 4 that the Z c value decreases with the increase of PMMA-b-P2VP content as the PMMA-b-P2VP concentration is below 50 mass%, indicating that the folding of PVDF chains is affected by the long-range glassy PMMA-b-P2VP in blends [52]. Meanwhile, the value of Z c almost remains unchanged as PMMA-b-P2VP concentration is over [53] found that the inclusion of amorphous polymer could reduce the crystallization rate of PVDF and make the spherulite less perfect, in agreement with our result.…”
Section: Jeziorny Methodsmentioning
confidence: 90%
“…They detected the competing melting with reorganization in individual PEO domains . In our previous work, we demonstrated the confinement effect on the crystallization kinetics in a wide temperature range in lamellar amorphous‐crystalline poly(ε‐caprolactone)‐ block ‐poly(4‐vinylpyridine) (PCL‐P4VP) block copolymer and found that even the local nucleation kinetics was affected by the confinement . Here, we are interested in extending our investigation on the detailed reorganization processes in this confined system.…”
Section: Introductionmentioning
confidence: 83%
“…The PCL‐P4VP block copolymer was synthesized via living ring opening polymerization (ROP) and atom transfer radical polymerization (ATRP) in sequence . The samples used here were the same as in Chen et al The characterization of the PCL homopolymer and the PCL‐P4VP copolymer is listed in Table .…”
Section: Methodsmentioning
confidence: 99%